Biodiversity: A Contribution to the Study of Medicinal Properties Hedychium coronarium Roscoe (Zingiberaceae) – distribution in Atlantic Forest: DOI: 10.15343/0104-7809.200630.4.18 - Dzimidas Rodrigues, Selma (2006)
In natural environment, as well as in cultures, chemical interactions appear among vegetable species, which influence seedgermination and species distribution. The present work aims to verify a possible allelophatic effect of Hedychium coronarium Roscoe(Zingiberaceae), white ginger, using cucumber plantlets as indicator to understand its distribution in the ecosystem. Hedychium coronariumis referred as having medicinal properties by the Juréia-Itatins’s populations and had many secondary metabolism compounds.For this experiment, we used aqueous extracts of H. coronarium 1:5 p/v in Petri dishes and filter paper as substratum for germination,with 10 replications containing each 10 cucumber seeds. The results showed that the aqueous extracts of H. coronarium inhibited thedevelopment of the radicle at 3 and 7 days of germination, as well as the length of the hypocotil. Total fresh and dry masses of thecucumber seedlings were not affected by white ginger extracts. Concerning these observations it can be concluded that there wasallelopathic effect of aqueous extracts of H. coronarium on the elongation of cucumber seedlings organs.